2011
DOI: 10.1111/j.1574-6968.2011.02217.x
|View full text |Cite
|
Sign up to set email alerts
|

SopB effector protein of Salmonella Typhimurium is translocated in mesenteric lymph nodes during murine salmonellosis

Abstract: Salmonella Typhimurium harbors two Salmonella pathogenicity islands (SPIs), each encoding a type three secretion system for virulence proteins. Although there is increasing evidence of postinvasion roles for SPI-1, it has been generally accepted that SPI-1 genes are downregulated following the invasion process. Here, we analyzed the expression and translocation of SopB in vitro, in cell culture and in vivo. To this end, a sopB-FLAG-tagged strain of Salmonella Typhimurium was obtained by epitope tagging. Tagged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Previously, the continued presence of T3SS1 effectors post-invasion has been explained by effector persistence in the intracellular environment [48] or delivery by the T3SS2 [25,26,49]. The main reason that the role of T3SS1 post-invasion is not well understood is because mutants lacking T3SS1 activity are unable to infect host cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the continued presence of T3SS1 effectors post-invasion has been explained by effector persistence in the intracellular environment [48] or delivery by the T3SS2 [25,26,49]. The main reason that the role of T3SS1 post-invasion is not well understood is because mutants lacking T3SS1 activity are unable to infect host cells.…”
Section: Discussionmentioning
confidence: 99%
“…SopB delivery by cytosolic bacteria requires continued transcription and translation of the molecule by the bacterium post-invasion [50]. Furthermore, T3SS2 has no role in delivery of SopB or SipA to infected host cells, although that has previously been suggested as a mechanism for sustained delivery both in vitro and in vivo [25,26,49]. Using a murine systemic infection model, we confirmed that SPI1 effectors are present in cells containing large numbers of cytosolic bacteria in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Animals received a high dose of Salmonella that, in turn, yielded a sufficient number of infecting bacteria (to be recovered to investigate SopB expression), and also provided an adequate amount of infected cells (to be isolated to determine SopB translocation). In a previous report, we demonstrated that 24 h after inoculation, SopB continues to be expressed by wild type infecting bacteria recovered from MLN [25]. Once again, intracellular Salmonella dam mutant expressed lower levels of SopB respect to the wild type strain ( p < 0.05) ( Fig.…”
Section: Sopb Synthesis and Translocation Is Impaired In Intracellulamentioning
confidence: 59%
“…We have shown earlier that Salmonella effectors involved in invasion processes continue to be expressed in vivo during systemic infection [25,34]. For instance, SopB protein was found in both phases of Salmonella infection [6,25]. However, the amount of SopB detected at day 5 was lower than that observed in bacteria recovered at 12 h postintraperitoneally inoculation [34,35].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation